PRODUCTION OF SUPEROXIDE IN THE SMALL INTESTINE OF RATS OF HYPO- AND HIPERMELATONINEMIA - Anasevych, Y.M.; Tsebrzhynskyy, O.I. (World of Medicine and Biology, 2012)
Hypomelatoninemia over the 30 days (clock lighting 1000-1500 lux) increases the production of superoxideanionradical from phagocytic electron-transport chains, hipermelatoninemia over the 30 days (retention of rats in the dark and oral administration of melatonin in the daily dose of 1 mg/kg of body weight) – from mitochondrial oxidation, that responsible the antioxidant properties of melatonin. Leak superoxide from the microsomal electron-transport chain oxidation in the both cases didn't change.
Keywords: small intestine; superoxidanionradical; hipomelatoninnemia; hypermelatoninnemia